Implementation of the Independent Curriculum in Fiqh Learning at MA Al-Fatah Palembang - Dinda Rizqiya; Tiara Wulandari; Muhamad Fauzi; Widya Wulandari (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to examine the implementation of the Independent Curriculum in fiqh learning at MA Al-Fatah Palembang. It focuses on learning planning, teaching strategies, assessment practices, and how the curriculum supports relevant, contextual, and student-centered learning experiences. Methodology: This study employed a descriptive qualitative research method. Data were collected through classroom observations, interviews with one fiqh teacher at MA Al-Fatah Palembang, and documentation review of teaching modules, learning objectives, and instructional plans. Data analysis used the interactive model consisting of data reduction, data display, and conclusion drawing. Main Findings: The findings indicate that the Independent Curriculum was implemented through adaptive, contextual, and student-centered fiqh learning. Teachers developed teaching modules, applied discussion, lecture, presentation, and project-based learning methods, and connected fiqh topics with daily life. Assessment covered cognitive, affective, and psychomotor domains. Although challenges such as students' lack of focus when using digital devices were identified, school support and teacher innovation contributed to effective learning implementation. Novelty/Originality of this study: This study provides an in-depth description of how the Independent Curriculum is implemented in fiqh learning at MA Al-Fatah Palembang. It highlights the integration of contextual fiqh instruction, flexible teaching modules, comprehensive assessment, and student-centered strategies. The study enriches knowledge on practical curriculum implementation in Islamic education and offers insights for improving fiqh learning effectiveness.